Economics of development - Gillis, Malcolm; Roemer, Michael; Snodgrass, Donald R.; Perkins, Dwight H. (New York : W. W. Norton, 1996)
Introduction. Starting modern economic growth. Growth and structural change. Development and human welfare. Guiding development. Planning models...
Keywords: Economics; Economic development; Developing countries -- Economic policy